Microbial population of palm oil mill effluent (POME) and efficiency of selected isolates in biogas production - Aigbodion, A.I.; Ogbebor, O.N.; Ikhuoria, E.U.; Omorogbe, S.O.; Maliki, M. (Journal of Plantation Crops, 2014)
A study was conducted to determine the microbial population suitable for enhanced anaerobic digestion of industrial effluents from Nigeria Institute for Oil Palm Research (NIFOR), Presco Oil Palm Plc, and Guinness Nigeria Plc. The standard dilution methods were used for recovery of bacteria and fungi. Isolation and quantity of colony-forming unit per mL (cfu mL-1) was assessed using the 10-fold serial dilution method. Significant differences were recorded with the bacterial concentrations in the three sampled effluents. Effluent from Presco had the highest bacteria cfu mL-1. Effluent from NIFOR consistently had the highest fungal population (cfu mL-1). Effluent from Guinness had the least fungal cfu mL-1. Two types of bacteria were recorded from the three effluents sampled. Similarly, seven types of fungi were present in the effluents from the three different locations. Inoculation of POME digester with the pure culture of the two bacteria led to a significant (about 5-fold) increase in the yield of biogas from the anaerobic digestion of POME; while inoculation with a consortium of bacteria at 20 per cent application yielded higher volume of biogas thereby indicating a kind of synergy between the two bacteria.